1998
DOI: 10.1029/98jb01491
|View full text |Cite
|
Sign up to set email alerts
|

Stress coupling between earthquakes in northwest Turkey and the north Aegean Sea

Abstract: Abstract. We have investigated the Coulomb stress interactions of 29 earthquakes (Ms > 6.0) that have occurred in the region of northwest Turkey and north Aegean Sea since 1912. Of these events, 23 may be related to earlier events, and 16 are clearly related to earlier events. All events at•er 1967 are related to previous events. Events in the early part of our time interval that show no correlation could be related to historical events as yet unidentified. In some cases, faults that have received a stress red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
158
0
18

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(181 citation statements)
references
References 55 publications
5
158
0
18
Order By: Relevance
“…There is now evidence that static stress changes may advance (retard) the time of large earthquakes and although the consensus from hitherto large scale observational studies is that both near and far field earthquake triggering is identified by periods of increased seismicity rates, there's no definitive information as to the rise and decay modes of such changes (for instance see Reasenberg and Simpson, 1992;Dieterich, 1994;Stein et al, 1997;Toda et al, 1998;Nalbant et al, 1998). The situation is aggravated in the case of far field triggering, where limited observational data exists, with contradictory (e.g.…”
Section: The Critical Point Earthquake Modelmentioning
confidence: 99%
“…There is now evidence that static stress changes may advance (retard) the time of large earthquakes and although the consensus from hitherto large scale observational studies is that both near and far field earthquake triggering is identified by periods of increased seismicity rates, there's no definitive information as to the rise and decay modes of such changes (for instance see Reasenberg and Simpson, 1992;Dieterich, 1994;Stein et al, 1997;Toda et al, 1998;Nalbant et al, 1998). The situation is aggravated in the case of far field triggering, where limited observational data exists, with contradictory (e.g.…”
Section: The Critical Point Earthquake Modelmentioning
confidence: 99%
“…These two earthquakes were the latest in a series of 11 M w Ͼ6.7 shocks during the last century that broke most of the NAFZ from the Karliova triple junction to the Aegean Sea, a distance of more than 1000 km (Ambraseys, 1970;Barka, 1999). The progression of earthquake activity to the east of the Marmara Sea has been modeled in terms of stress transfer and release (Stein et al, 1997;Nalbant et al, 1998). In these models the static stress field induced by each large coseismic shock is oriented such that nearby fault segments are promoted toward failure by an increase in their Coulomb failure stress.…”
Section: Introductionmentioning
confidence: 99%
“…Calculations were performed for the whole area, although coseismic slip alters the stress state in a limited area, depending upon the magnitude of the modeled event. ΔCFF is calculated from (5) with μ΄ set to 0.4 (Stein et al, 1997;Nalbant et al, 1998). Shear modulus G, is assumed to be 33GPa and Poisson ratio 0.25 (Papadimitriou & Sykes, 2001).…”
Section: Coulomb Stress Changes Calculationsmentioning
confidence: 99%